ANALISIS PROFITABILITAS DAN LIKUIDITAS TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yanti, Sri; Prima, Argo Putra (SCIENTIA JOURNAL, 2021)
The purpose of this study is to determine the effect of profitability and liquidity on financial distress in manufacturing companies listed on the Indonesia Stock Exchange. The data studied were obtained from the Indonesia Stock Exchange in the form of audited annual financial reports from 2015 to 2019. The sampling method used purposive sampling, namely data collection techniques using certain criteria. The sample of this study consisted of 9 companies from 31 companies that have been listed on the Indonesia Stock Exchange. This study uses SPSS (Statistical Package for the Social Sciencess) application version 25 to analyze the effect of independent variables on the dependent variable. The results of the conclusions of this study indicate that all variables pass the classical assumption test and are suitable for use as research data, the results of the t statistical test show that Return on Assets partially does not have a significant effect on Earning per Share, Net Profit Margin has a significant effect on Earning per Share and Current The ratio has a significant negative effect on Earning per Share.